Variations in cosmic rays and the surface electric field in January 2016 - Makhmutov, V. S. (2017)
Three units of neutron detectors and four blocks of gamma-ray spectrometers have been installed and started operation at Complejo Astronomico El Leoncito, CASLEO (San Juan, Argentina; coordinates 31 S, 69 W; height of 2550 m; the rigidity of geomagnetic cutoff of Rc = 9.7 GV) in May 2015 as part of the scientific cooperation between the Lebedev Physical Institute, Russian Academy of Sciences (Moscow, Russia), Universidade Presbiteriana Mackenzie (San Paulo, Brazil) and Complejo Astronomico El Leoncito, CASLEO (San Juan, Argentina). Measurements with the new detectors greatly supplement the experimental data on variations in the charged component of cosmic rays obtained by the CARPET ground-based cosmic ray detector in 2006. The first results from a joint analysis of new experimental data are presented. Particular attention is given to growing cosmic ray fluxes associated with changes in the surface electric field. The main characteristics of the events recorded in January 2016 are presented.